Facilitating translocation: an endangered rodent engineer improves outcomes for re-introduced San Joaquin antelope squirrels - Patrick Anderson; Craig Fiehler; William Timothy Bean (California Fish and Wildlife Journal)
Despite the popularity of translocation for conservation, many wildlife translocations fail. Research on translocation failure has most often focused on negative species interactions like competition or predation, but positive interactions such as facilitation may be just as important. Ecosystem engineers, including burrowing rodents, play a key role in maintaining high levels of biodiversity and could be used to improve translocation outcomes. However, ecosystem engineers might simultaneously facilitate and compete with translocated species. We used a natural experiment to assess translocation outcomes with a soft release for the threatened San Joaquin antelope squirrel (Ammospermophilus nelsoni) at a site with and without giant kangaroo rats (Dipodomys ingens)—an endangered species and ecosystem engineer. We further compared these outcomes to a control, non-translocated population of antelope squirrels. Survival was highest at the control site, lower at the site with giant kangaroo rats present, and lowest at the site with no giant kangaroo rats. In the year following translocation, we found evidence of reproduction at all three sites. After four years, the antelope squirrel population re-introduced to the kangaroo rat present site persisted, but the population at the kangaroo rat absent site appears to have failed. Home range sizes were much larger at the translocation sites compared to the control. Antelope squirrels dispersed farther from initial release at the site with giant kangaroo rats than the site without, but these results may have suffered from survivorship bias—that is, squirrels at the kangaroo rat absent site either stayed directly within the release footprint or dispersed so far that we could not find them. Our results suggest that the positive impacts of a burrowing ecosystem engineer outweigh the potential negative impacts from competition.